DETERMINAN VARIABEL INFLASI DAN NILAI TUKAR TEHADAP PEMBIAYAAN PERBANKAN SYARIAH DENGAN PERTUMBUHANEKONOMI SEBAGAI VARIABEL MODERATING - Arifa Pratami (STAI Syubbanul Wathon Magelang, 2018)
The purpose of this study is to analyze the determination ofinflation and exchange rates on the financing of Islamic banking witheconomic growth as a moderating variable. This study uses secondarydata taken entirely from official sources in monthly form starting fromJanuary 2010 to December 2017. Data sources for Non PerformingFinancing (NPF), Third Party Funds (TPF) and financing are obtainedfrom Bank Indonesia Sharia Banking Statistics ( SPS-BI) and Statisticson Islamic Banking of the Financial Services Authority (SPBS / OJK).Sources of inflation data and exchange rates are obtained from BI'sofficial website (www.bi.go.id), and the Industrial Production index(IPI) data source as a proxy for economic condition data accessed fromthe official BPS website (www.bps.go.id) . The results of the studyfound that inflation had a positive but not significant effect onfinancing channeled by Islamic banking, the rupiah exchange rate had anegative and significant influence on the financing of Islamic banking.Economic growth is not able to moderate the relationship betweeninflation and financing of Islamic banking, economic growth is able tomoderate the relationship between exchange rates on Islamic bankingfinancing.